2009
DOI: 10.1073/pnas.0902578106
|View full text |Cite
|
Sign up to set email alerts
|

Protein targeting into secondary plastids of chlorarachniophytes

Abstract: Most plastid proteins are encoded by the nuclear genome, and consequently, need to be transported into plastids across multiple envelope membranes. In diverse organisms possessing secondary plastids, nuclear-encoded plastid precursor proteins (preproteins) commonly have an N-terminal extension that consists of an endoplasmic reticulum (ER)-targeting signal peptide and a transit peptide-like sequence (TPL). This bipartite targeting peptide is believed to be necessary for targeting the preproteins into the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…2E). This localization pattern is identical to the localization observed previously for PPC and nucleomorph proteins (Hirakawa et al, 2009;.…”
Section: In Vivo Subcellular Localization Of B Natans Hisrss and Glyrsssupporting
confidence: 73%
See 1 more Smart Citation
“…2E). This localization pattern is identical to the localization observed previously for PPC and nucleomorph proteins (Hirakawa et al, 2009;.…”
Section: In Vivo Subcellular Localization Of B Natans Hisrss and Glyrsssupporting
confidence: 73%
“…To construct plasmids encoding GFP-tagged aaRSs, target cDNA fragments were amplified by PCR with specific primer sets (shown in supplementary material Table S5), and each fragment was inserted between the HindIII and NcoI site of the pLaRGfp+mc vector (Hirakawa et al, 2009). To introduce substitutions into some target fragments, we used PCR-based site-directed mutagenesis technique (Higuchi et al, 1988).…”
Section: In Vivo Gfp Targeting Analysismentioning
confidence: 99%
“…Such protein import has been already experimentally proven in apicomplexans (Waller et al, 1998), diatoms , euglenozoans (Shashidhara et al, 1992), dinoflagellates (Nassoury et al, 2003), cryptophytes (Gould et al, 2006), and chlorarachniophytes (Hirakawa et al, 2009). Since phylogenies based on both nuclear and plastid genes congruently place C. velia within chromalveolates close to apicomplexan parasites (Janouš kovec et al, 2010), it is bordering on certainty that the same targeting mechanism operates in C. velia as well.…”
Section: Predicted Subcellular Location Of C Velia Tetrapyrrole Biosmentioning
confidence: 99%
“…To construct two GFP expression vectors, cDNA fragments of two Der1-like genes (BnDer1-49642 and BnDer1-92850 genes) were amplified by PCR with specific primers shown in Table S2 in the supplemental material, and then each fragment was inserted between HindIII and NcoI sites of the pLaRGfpϩmc vector (33). These plasmids were cloned in the DH5␣ strain of Escherichia coli and purified with a QIAprep Spin miniprep kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…Plastid preproteins of chlorarachniophytes, like those of other secondary algal groups, possess an N-terminal bipartite targeting sequence consisting of an SP and a TPL sequence (54). Our previous studies demonstrated that the preproteins are transported into the plastids via the ER and that a net positive charge of TPL sequences is essential for passing through the inner two plastid membranes (31,33). This suggests the existence of translocons that selectively recognize the TPL sequence and facilitate preprotein transport across the two inner plastid membranes.…”
mentioning
confidence: 99%